2007
DOI: 10.1021/cc070015u
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Enhanced One-Pot Synthesis of Diversified 3-Acyl-5-Hydroxybenzofurans

Abstract: An efficient one-pot two-step synthesis of diversified 3-acyl-5-hydroxybenzofurans under microwave irradiation is described. The desired products were synthesized rapidly by adopting the Nenitzescu reaction of enaminones and benzoquinones. This methodology provides us with high proportion of desired products in the crude mixture with short reaction times. These two advantages are especially favorable for generating compound libraries in high-throughput biological screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Another method that has been used to synthesize benzoyl­benzofurans devoid of substituents at C-2 is the conjugate addition of enamino­ketones to 1,4-benzoquinones. The latter method was employed in this study because it utilizes readily available starting acetophenones and benzoquinones and also affords the 3-benzoyl­benzofurans in a few steps and in good yields. As shown in Scheme , the synthesis was initiated by reacting the TBDMS-protected acetophenone 8 with N,N -dimethylformamide dimethylacetal (DMF–DMA) followed by benzoquinone in HOAc. This gave the benzoylbenzofuran 9 in a low yield and the chromone 11 in a high yield .…”
Section: Resultsmentioning
confidence: 99%
“…Another method that has been used to synthesize benzoyl­benzofurans devoid of substituents at C-2 is the conjugate addition of enamino­ketones to 1,4-benzoquinones. The latter method was employed in this study because it utilizes readily available starting acetophenones and benzoquinones and also affords the 3-benzoyl­benzofurans in a few steps and in good yields. As shown in Scheme , the synthesis was initiated by reacting the TBDMS-protected acetophenone 8 with N,N -dimethylformamide dimethylacetal (DMF–DMA) followed by benzoquinone in HOAc. This gave the benzoylbenzofuran 9 in a low yield and the chromone 11 in a high yield .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the reactions of enaminones of type 1 with quinones were known to provide 5‐hydroxybenzofurans, wherein the attack of the O‐nucleophilic site to the C–N bond in tertiary enaminones allowed the benzofuran annulations. After the primary investigation of Elnagdi et al,44 Liu and co‐worker45 reported their systematic work on the microwave‐assisted synthesis of the hydroxybenzofurans 87 via the reactions of tertiary enaminones and benzoquinones 86 (Scheme ).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Microwave irradiation technology in organic synthesis is a powerful tool for drug synthesis as it can speed up the reactions under mild conditions allowing the rapid preparation of compounds. 30 As mentioned above, microwave irradiation technology has been successfully applied to the synthesis of N-arylthieno [2,3-d] 33 by microwave irradiation technology (Figure 4).…”
Section: Introductionmentioning
confidence: 99%